The Strategic Role of Sales Management for Market Access in the Pharmaceutical Sector - Lucrezia Maria de Cosmo (European Scientific Journal, ESJ, 2018)
In this paper we analyze the evolution of the role of the sales manager and of the sales force in a relational perspective of value creation in businessto- business contexts, included in the sale of prescription drugs, in Italy. The empirical research and the strategic implications are to highlight the importance of the customer-supplier relationship in business to business context and the role of the sales force in managing long-lasting relationships with customers. The work ends with the study of a task force model for easier market access by pharmaceutical companies and an expected value proposition through the sharing of knowledge and the creation of partnerships.